Domain Dependent Fermi Arcs Observed in a Striped Phase Dichalcogenide. Issue 9 (10th July 2022) - Mizokawa, Takashi; Barinov, Alexei; Kandyba, Viktor; Giampietri, Alessio; Matsumoto, Ryoya; Okamoto, Yohei; Takubo, Kou; Miyamoto, Koji; Okuda, Taichi; Pyon, Sunseng; Ishii, Hiroyuki; Kudo, Kazutaka; et al.
Abstract: Solids undergoing symmetry breaking phase transitions commonly exhibit domains of low symmetry phases with various sizes and morphological shapes. Usually, the shapes of these domains are not directly related to the nature of symmetry breaking. Here, an interesting example of a layered dichalcogenide with a triangular lattice is shown, in which symmetry breaking of electronic charge/orbital is accompanied by formation of striped domains and exotic surface states with peculiar spin textures. Using angle‐resolved photoemission spectromicroscopy, the mesoscopic striped domains in the layered IrTe2 are observed across the first order phase transition at ≈280 K. Under further cooling down to 47 K, the striped domains evolve into trijunction domains with electronic anisotropy in three directions. Each domain harbors quasi 1D surface bands forming fragmented Fermi surfaces (Fermi arcs) with peculiar spin polarization revealed by spin‐resolved photoemission spectroscopy. The Fermi arc corresponds to an edge state of the 2D bulk electronic bands truncated at the surface, indicating an interesting interplay between the symmetry breaking, surface electronic structure, and the spin state. Abstract : Photoemission spectromicroscopy on a layered Ir ditelluride shows that striped symmetry breaking of electrons is accompanied by striped or trijunction domain textures. Domain dependent surface bands provide fragmented Fermi surfaces with peculiar spin‐momentum locking as revealed by spin‐resolved photoemission spectroscopy. These results indicate that the spin polarized surface states of the Ir ditelluride can be controlled by domain engneering.